2012
DOI: 10.4236/aim.2012.22019
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biochemical Characterization of Native and Pegylated Form of L-Asparaginase from <i>Aspergillus terreus</i> and Evaluation of Its Antiproliferative Activity

Abstract: L-asparaginase is a chemotherapeutic drug used in the treatment of lymphoblastic leukemia. In the present study, the extracellular L-asparaginase produced by strain (PC-1.7.A) of Aspergillus terreus was purified, characterized, and modified with polyethylene glycol. Moreover, its antiproliferative activity was evaluated. The apparent molecular weight of the enzyme was found to be 136 kDa. The optimal pH and temperature for the enzyme were 9.0˚C and 40˚C, respectively. The enzyme retained 100% of the activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The E. coli (EcA II) and E. chrysanthemi (ErA) ASNases hydrolyzes L-glutamine up to 9% of total hydrolysis activity (high preference for L-Asn over L-Gln). Therefore, innumerable approaches to obtain ASNase with lower glutaminase activity have been investigated, such as bioprospecting other microbial sources or the modification of commercial ASNases by site-directed mutagenesis (Loureiro et al, 2012; Ardalan et al, 2018). Amino acids essential for biocatalysis in most cases were not altered since they are obligatory for effective ASNase binding to asparagine.…”
Section: Protein Engineering For Improvement Of L-asparaginase Therapmentioning
confidence: 99%
“…The E. coli (EcA II) and E. chrysanthemi (ErA) ASNases hydrolyzes L-glutamine up to 9% of total hydrolysis activity (high preference for L-Asn over L-Gln). Therefore, innumerable approaches to obtain ASNase with lower glutaminase activity have been investigated, such as bioprospecting other microbial sources or the modification of commercial ASNases by site-directed mutagenesis (Loureiro et al, 2012; Ardalan et al, 2018). Amino acids essential for biocatalysis in most cases were not altered since they are obligatory for effective ASNase binding to asparagine.…”
Section: Protein Engineering For Improvement Of L-asparaginase Therapmentioning
confidence: 99%
“…Similar effect was observed when l -asparaginase from deuteromycetes Fusarium tricinctum was purified which regressed lymphosarcoma in mice (Scheetz et al 1971). Later purified extracellular l -asparaginase from A. terreus was conjugated with polyethylene glycol and it did not indicate any glutaminase activity (Loureiro 2012). Sarquis et al examined Aspergillus tamari and A. terreus for l -asparaginase production and found that asparaginase activity is reduced in the presence of urea and glutamine (Sarquis et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, fungal sources have been explored for their eukaryotic nature, as their similarity to humans at cellular level could reduce the unwanted immunological reactions [36,37]. Several reports [38][39][40][41] and comprehensive reviews [20, [42][43][44] have been published, revealing the potential of fungi as a feasible source of ASNase and presenting antitumor activity [45,46]. In addition to being eukaryotes, they can produce ASNase with reduced glutaminase activity [47,48].…”
Section: Introductionmentioning
confidence: 99%